Assessing the coordination of regional water and soil resources and ecological-environment system based on speed characteristics. (10th March 2022) - Cheng, Kun; He, Kangxu; Fu, Qiang; Tagawa, Kotaro; Guo, Xinxin
Abstract: The evaluation of the coordination of regional water and soil resources and ecological environment systems from the perspective of speed characteristics is more conducive to decision-makers to understand the development status of water and soil resources and ecosystems in a timely manner. In this paper, taking Heilongjiang Province, the main grain producing area of China, as an example, 25 main indices are screened based on agricultural production factors and the weight of each index is determined by the information entropy, the speed characteristics of each index is characterized by the average annual growth rate. The coupling-coordination index of system development is determined by the vector angle and projection, and compare and analyze the coupling-coordination index between the result and the original data. The results show that the water and soil resources ecological environment system was in a relatively weak coupling stage of barely coordination, the coordinated development level of the system is low during the study period. In comparison with the original data results, the coupling and coordination of the system are better reflected by the calculation method using speed characteristics, and the calculation results of speed characteristics are ahead of time, which is more conducive to the timely assessment of the development of the water and soil resources ecological-environment system. Highlights: To conduct an evaluation of the coordination of environment from the perspective of development rate characteristics. To use annual growth rate to characterize the development rate characteristics of various indicators. To use vector included angle and projection to determine the coupling and coordination indices of the system's development.